Citizen Science and Youth Audiences: Educational Outcomes of the Monarch Larva Monitoring Project - Dina L. Kountoupes; Karen S. Oberhauser (The University of Alabama, 2022)
Citizen science projects in which members of the public participate in large scale science research programs are excellent ways for universities to engage the broader community in authentic science research. The Monarch Larva Monitoring Project (MLMP) is such a project. It involves hundreds of individuals throughout the United States and southern Canada in a study of monarch butterfly distribution and abundance. This program, run by faculty, graduate students, and staff at the University of Minnesota, provides research opportunities for volunteer monitors. We used mixed methods to understand contexts, outcomes, and promising practices for engaging youth in this project. Slightly over a third of our adult volunteers engaged youth in monitoring activities. They reported that the youth were successful at and enjoyed project activities, with the exception of data entry. Adults innovations increased the success and educational value of the project for children without compromising data integrity. Many adults engaged in extension activities, including independent research that built on their monitoring observations. This project provides an excellent forum for science and environmental education through investigation, direct and long-term interactions with natural settings, and data analysis.